Spot‐scanning hadron arc (SHArc) therapy: A proof of concept using single‐ and multi‐ion strategies with helium, carbon, oxygen, and neon ions. Issue 9 (11th July 2022) - Mein, Stewart; Kopp, Benedikt; Tessonnier, Thomas; Liermann, Jakob; Abdollahi, Amir; Debus, Jürgen; Haberer, Thomas; Mairani, Andrea
Abstract: Purpose: To present particle arc therapy treatments using single and multi‐ion therapy optimization strategies with helium ( 4 He), carbon ( 12 C), oxygen ( 16 O), and neon ( 20 Ne) ion beams. Methods and materials: An optimization procedure and workflow were devised for spot‐scanning hadron arc therapy (SHArc) treatment planning in the PRECISE (PaRticle thErapy using single and Combined Ion optimization StratEgies) treatment planning system (TPS). Physical and biological beam models were developed for helium, carbon, oxygen, and neon ions via FLUKA MC simulation. SHArc treatments were optimized using both single‐ion ( 12 C, 16 O, or 20 Ne) and multi‐ion therapy ( 16 O+ 4 He or 20 Ne+ 4 He) applying variable relative biological effectiveness (RBE) modeling using a modified microdosimetric kinetic model (mMKM) with ( α / β )x values of 2, 5, and 3.1 Gy, respectively, for glioblastoma, pancreatic adenocarcinoma, and prostate adenocarcinoma patient cases. Dose, effective dose, linear energy transfer (LET), and RBE were computed with the GPU‐accelerated dose engine FRoG and dosimetric/biophysical attributes were evaluated in the context of conventional particle and photon‐based therapies (e.g., volumetric modulated arc therapy [VMAT]). Results: All SHArc plans met the target optimization goals (3GyRBE) and demonstrated increased target conformity and substantially lower low‐dose bath to surrounding normal tissues than VMAT. SHArc plans using a singleion species ( 12 C, 16 O, or 20 Ne) exhibited favorable LET distributions with the highest‐LET components centralized in the target volume, with values ranging from ∼80–170 keV/μm, ∼130–220 keV/μm, and ∼180–350 keV/μm for 12 C, 16 O, or 20 Ne, respectively, exceeding mean target LET of conventional particle therapy ( 12 C:∼55, 16 O:∼75 20 Ne:∼95 keV/μm). Multi‐ion therapy with SHArc delivery (SHArcMIT ) provided a similar level of target LET enhancement as SHArc compared to conventional planning, however, with additional benefits of homogenous physical dose and RBE distributions. Conclusion: Here, we demonstrate that arc delivery of light and heavy ion beams, using either a single‐ion species ( 12 C, 16 O, or 20 Ne) or combining two ions in a single fraction ( 16 O+ 4 He or 20 Ne+ 4 He) affords enhanced physical and biological distributions (e.g., LET) compared with conventional delivery with photons or particle beams. SHArc marks the first single‐ and multi‐ion arc therapy treatment optimization approach using light and heavy ions.